Growth scaling for the early dynamics of HIV/AIDS epidemics in Brazil and the influence of socio-demographic factors. (7th April 2018) - Dinh, L.; Chowell, G.; Rothenberg, R.
Highlights: The generalized-growth model is a useful tool to characterize variability in epidemic growth patterns at different spatial scales. The growth scaling of the early dynamics of the HIV/AIDS epidemic in Brazil displayed substantial variation across states. Socio-demographic factors were significantly associated with the growth scaling of the early dynamics of the HIV/AIDS epidemic at state level in Brazil. Abstract: The early dynamics of an infectious disease outbreak can be affected by various factors including the transmission mode of the disease and host-specific factors. While recent works have highlighted the presence of sub-exponential growth patterns during the early phase of epidemics, empirical studies examining the contribution of different factors to early epidemic growth dynamics are lacking. Here we aim to characterize and explain the early incidence growth patterns of local HIV/AIDS epidemics in Brazil as a function of socio-demographic factors. For this purpose, we accessed annual AIDS incidence series and state-level socio-demographic variables from publicly available databases. To characterize the early growth dynamics of the HIV/AIDS epidemic, we employed the generalized-growth model to estimate with quantified uncertainty the scaling of growth parameter ( p ) which captures growth patterns ranging from constant incidence ( p = 0 ) to sub-exponential (0 <  p  < 1) and exponential growth dynamics ( p = 1 ) at three spatial scales: national, regional, and state levels. We evaluated the relationship between socio-demographic variables and epidemic growth patterns across 27 Brazilian states using mixed-effect regression analyses. We found wide variation in the early dynamics of the AIDS epidemic in Brazil, displaying sub-exponential growth patterns with the p parameter estimated substantially below 1.0. The mean p was estimated to be 0.81 at the national level, with a range of 0.72–0.85 at the regional level, and a range of 0.28–0.96 at the state level. Our findings support the notion that socio-demographic factors contribute to shaping the early growth dynamics of the epidemic at the local level. Gini index and socio-demographic index were negatively associated with the parameter p, whereas urbanicity was positively associated with p . The results could have theoretical significance in understanding differences in growth scaling across different sexually transmitted disease systems, and have public health implications to guide control.